PREDIKSI HARGA CRYPTOCURRENCY DENGAN METODE K-NEAREST NEIGHBOURS - Fatah, Haerul; Subekti, Agus (Jurnal Pilar Nusa Mandiri, 2018)
Electronic money is getting more popular as online transaction means among people especially for entrepreneurs, businessmen and investors due to its practicality. Cryptocurrency emerges as the solution to resolve the contrains of electronic money that depends heavily on third parties. One of widely used Cryptocurrency is Bitcoin. The price of bitcoin fluctuates in very short duration. It is similar with the fluctuation of stock price in stock market. Prediction for future price becomes important anad interesting. In this paper, we propose a prediction model for cryptocurrency price. Out proposed model predict the cryptocurreny price using KNN (K-Nearest Neighbors) method. With the parameter of k=3 and using linear NN search algorithm, out proposed method gives a mean absolute error (MAE) of 0.0018 and root mean squared error (RMSE) of 0.0089.